Perinatal Outcomes According to the Type of Prenatally Diagnosed Umbilical-Portal-Systemic Venous Shunt - Jinha Chung; Jihye Koh; Mi-Young Lee; Hye-Sung Won (Clinical and Experimental Obstetrics & Gynecology)
Background: The abnormal course of the umbilical vein and the absence or displacement of the portal vein or ductus venosus may suggest the presence of other shunts. In recent years, an in utero classification of umbilical-portal-systemic venous shunts (UPSVS) has been introduced. This study aims to report our experience with the prenatal diagnosis of UPSVS and to evaluate the perinatal outcomes of fetuses with different types of UPSVS. Methods: This was a retrospective study of fetuses prenatally diagnosed with UPSVS between January 2005 and September 2020 at Asan Medical Center. UPSVS was prenatally classified into three types according to the anatomical origin of the shunt: type I, umbilical-systemic shunt; type II, ductus venosus-systemic shunt; and type III, portal-systemic shunt. Type III was further divided into two subtypes: type IIIa, intrahepatic shunt; type IIIb, extrahepatic shunt. Postnatal ultrasonography or abdominal computed tomography (CT) was performed to confirm UPSVS. Results: Out of 18 fetuses prenatally diagnosed with UPSVS, four were excluded. All four patients were confirmed to have portal vein variations without a shunt. The median gestational age at the diagnosis of the remaining 14 fetuses was 30.3 weeks (range, 23.1–37.3). The median gestational age at birth was 37.2 weeks (range, 31.0–39.3), and the median birth weight was 2105 g (range, 1350–2870), including nine (64%) who had body weights below the 10th percentile. Eleven patients (79%) had combined anomalies; cardiomegaly and fetal hydrops were observed in eight (57%) and two (14%) patients, respectively. Among the 11 patients who underwent chromosomal analysis, three had abnormal results. Two infants with abnormal karyotypes died. The most common type was type I (8, 57%), followed by type IIIa (4, 29%), type II (1, 7%), and type IIIb (1, 7%). In type I, all but one patient had structural anomalies; five (63%) showed cardiomegaly and five (63%) were associated with growth restriction. Nevertheless, half of the patients survived without major anomalies. In type IIIa, three (75%) patients were associated with growth restriction, but they showed catch-up growth after birth. All patients had mild transient hyperammonemia. One type II patient was associated with cardiomegaly, fetal hydrops, and an abnormal karyotype. One type IIIb patient had multiple anomalies and an abnormal karyotype. No surgical correction was required because of the UPSVS. Conclusions: Prenatal diagnosis of UPSVS is feasible. When an abnormal course of the umbilical or portal vein is detected on the transverse abdominal view, UPSVS should be suspected. UPSVS is commonly associated with structural anomalies, chromosomal anomalies, growth restriction, and cardiomegaly. UPSVS without associated anomalies may have a favorable prognosis. Our study can help predict the prognosis of UPSVS and assist in prenatal counseling.